Constitutional Interpretation Within Islamic and Western Legal Frameworks - Muh Ibnu Sholeh; Siti Fatinnah Binti Ab Rahman (Badan usaha Milik Desa Berkaho Pungpungan, 2025)
This study examines the mechanisms of constitutional interpretation within Islamic and Western legal traditions, focusing on their foundational principles, interpretive tools, and institutional actors. Western constitutional systems are typically grounded in secularism, liberal democracy, and popular sovereignty, where interpretation evolves through judicial reasoning, often guided by theories such as originalism, textualism, or living constitutionalism. In contrast, Islamic constitutionalism draws legitimacy from divine revelation, with the Qur’an and Sunnah forming the core sources of law. Interpretation in Islamic legal frameworks involves usul al-fiqh, maqasid al-shariah, and ijtihad, aiming to preserve divine intent while addressing contemporary realities. Using a library research method, this paper analyzes key differences and points of convergence between the two systems. It finds that Western systems grant primary interpretive authority to courts, while Islamic models often involve religious scholars alongside state institutions. The flexibility of interpretation also varies, with Western systems emphasizing legal evolution, whereas Islamic systems emphasize preservation of ethical and theological principles. This study contributes to the discourse on legal pluralism, highlighting challenges and opportunities in integrating Islamic and constitutional norms. It offers insights for legal scholars, policymakers, and constitutional drafters working within or across pluralistic legal environments in Muslim-majority countries.